Reliability Analysis of Electrotechnical Devices - Tan, Cher Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a book on the practical approaches of reliability to electrotechnical devices and systems. It includes the electromagnetic effect, radiation effect, environmental effect, and the impact of the manufacturing process on electronic materials, devices, and boards.